Ecological aspects of 99Mo/99mTc production at an electron accelerator - Dikiy, N.P.; Lyashko, Yu.V.; Uvarov, V.L.; Shlyakhov, I.N.; Malets, Eu.B. (Вопросы атомной науки и техники, 2004)
The present report deals with experimental investigations into possible processes of accumulation of radioactive by-products (RBPs) during 99Mo/99mTc production at an electron linac. Foils from natural molybdenum (a target) and a number of typical target setup materials (Al, Ti, Cu, Ta, Ni and stainless steel) were chosen as an object of investigations. The generation of radionuclides in the samples was performed in identical conditions under secondary radiation (bremsstrahlung + photoneutrons) of the linac LU-20 in a typical range of electron energies from 24 to 34 MeV.